2017
DOI: 10.1002/ejp.1032
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of clobazam in chronic low‐back pain but not in experimentally induced pain

Abstract: Modulation of GABAergic pain-inhibitory pathways may be a potential future therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Forty‐nine patients were therefore analysed (29 women, mean age 54.3 years, SD 15.8). A significant analgesic effect was found in the supine, but not in the sitting position (treatment effect compared to placebo: 0.7, 95%‐CI 0.2 to 1.1, p = 0.003), which is the object of a separate publication (Schliessbach et al., ). For supine pain, there were 29 responders in the verum session vs. 20 in the placebo session.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Forty‐nine patients were therefore analysed (29 women, mean age 54.3 years, SD 15.8). A significant analgesic effect was found in the supine, but not in the sitting position (treatment effect compared to placebo: 0.7, 95%‐CI 0.2 to 1.1, p = 0.003), which is the object of a separate publication (Schliessbach et al., ). For supine pain, there were 29 responders in the verum session vs. 20 in the placebo session.…”
Section: Resultsmentioning
confidence: 95%
“…These drugs were chosen to cover multiple modes of analgesic action. Oxycodone is a potent agonist at peripheral and central opioidergic pathways, imipramine is a modulator of noradrenergic neurotransmission and serotonergic neurotransmission in the central nervous system, and clobazam modulates spinal nociceptive inhibitory GABA‐ergic pathways (Zeilhofer et al., ; Vuilleumier et al., ; Schliessbach et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It was registered with clinicaltrials.gov (NCT01179828) and approved by the local ethics committee (KEK 213-09). The detailed study protocol [7] and results from another substudy [8] have been published. All participants gave written informed consent prior to enrolment.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, clinical trials performed on chronic lower-back pain patients have shown that CBZ and their metabolites are able to generate analgesia in humans (Besson et al, 2015;Schliessbach et al, 2017).…”
Section: Gaba a Rsmentioning
confidence: 99%